The essence of psychotherapy : reinventing the art in the new era of data - Cummings, Nicholas A. (Practical resources for the mental health professional., 2000)
The Essence of Psychotherapy traces the common thread in all psychotherapy approaches--behavioral, cognitive, psychodynamic, strategic, and humanistic--and defines this "essence" as a set of fundamental principles and ultimate objectives that must be preserved in the face of increased standardization in the field. While today's therapist is guided by protocols and manuals, psychotherapy, in practice, remains an art. Nicholas and Janet Cummings have gathered case studies of master therapists to illustrate the essential process of successful therapy and to show that, as an art, it is both teachable and verifiable. * Illustrated with case studies * Analyses the techniques of six master psychotherapists in their work with difficult patients